A Role for Sigma Receptors in Stimulant Self Administration and Addiction - Shang-Yi Tsai; Theresa Kopajtic; Takato Hiranita; Teruo Hayashi; Gianluigi Tanda; Jonathan L. Katz; Tsung-Ping Su (MDPI AG, 2011)
Sigma1 receptors (σ1Rs) represent a structurally unique class of intracellular proteins that function as chaperones. σ1Rs translocate from the mitochondria-associated membrane to the cell nucleus or cell membrane, and through protein-protein interactions influence several targets, including ion channels, G-protein-coupled receptors, lipids, and other signaling proteins. Several studies have demonstrated that σR antagonists block stimulant-induced behavioral effects, including ambulatory activity, sensitization, and acute toxicities. Curiously, the effects of stimulants have been blocked by σR antagonists tested under place-conditioning but not self-administration procedures, indicating fundamental differences in the mechanisms underlying these two effects. The self administration of σR agonists has been found in subjects previously trained to self administer cocaine. The reinforcing effects of the σR agonists were blocked by σR antagonists. Additionally, σR agonists were found to increase dopamine concentrations in the nucleus accumbens shell, a brain region considered important for the reinforcing effects of abused drugs. Although the effects of the σR agonist, DTG, on dopamine were obtained at doses that approximated those that maintained self administration behavior those of another agonist, PRE-084 required higher doses. The effects of DTG were antagonized by non-selective or a preferential σ2R antagonist but not by a preferential σ1R antagonist. The effects of PRE-084 on dopamine were insensitive to σR antagonists. The data suggest that the self administration of σR agonists is independent of dopamine and the findings are discussed in light of a hypothesis that cocaine has both intracellular actions mediated by σRs, as well as extracellular actions mediated through conventionally studied mechanisms. The co-activation and potential interactions among these mechanisms, in particular those involving the intracellular chaperone σRs, may lead to the pernicious addictive effects of stimulant drugs.